Eksplorasi Kepuasan Terhadap Pemenuhan Kebutuhan Dasar Manusia Berbasis Hirarki Maslow Pada Petani Garam di Desa Pinggir Papas, Kabupaten Sumenep - Novi Putri Cahyanti; Nurfika Asmaningrum; Alfid Tri Afandi (Lembaga Penelitian dan Pengabdian Masyarakat Universitas dr. Soebandi, 2023)
The basic human needs are satisfied when they are fully met. Maslow's theory classifies basic human needs into physiological needs, the needs for safety, the needs for belongingness and love, esteem needs, and self-actualization needs. This study analyzed the satisfaction of basic human needs in salt farmers in Pinggir Papas village, Kalianget district, Sumenep regency, Madurese Island. This descriptive study involved a sample group of 75 salt farmers selected through total sampling. Research data was collected using a need satisfaction inventory questionnaire. The results showed that the satisfaction of basic human needs among salt farmers was marked by a mean score of 194.51, meaning that the farmers had satisfied their basic needs. The satisfaction of basic needs was close to the maximum mean in each category, inter alia, physiological needs (36.79), the needs for safety (38.56), belongingness and love (39.85), self-esteem needs (39.75), and self-actualization needs (39.56). The study found the highest to lowest basic needs’ satisfaction were the needs for belongingness and love, self-esteem needs, and self-actualization, the needs for safety, and physiological needs. Nurses can act as educator and advocate to provide comprehensive information, advocacy to be motivated on the fulfillment of basic needs to ensure maximum satisfaction in each category of basic needs. Keyword: Basic Human Needs, Descriptive, Salt Farmers, Satisfaction